KARAKTERISTIK LAHAN UNTUK TANAMAN BAWANG PUTIH (Allium sativum L.) PADA INCEPTISOL DAN ALFISOL DI KECAMATAN PUJON, MALANG - Djodhi Indra Septiyan; S Soemarno (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2019)
The national production of garlic that is currently under fluctuations and could not fullfill demand for garlic that led Governments to perform the import. Land extensification for garlic in East Java, Pujon district, Malang is expected to be the solution to increase production. However, restricted by the limitations of the information of land characteristics that remains unclear, it takes effort to find out the land characteristics for garlic in the subdistrict of Pujon. Research was carried out for gathering information of land characteristic and to analyze relationships between land characteristics and garlic production. This study was carried out using survey method include groundcheck, minipit observation, soil sampling, and interviews to the farmers. Then, post survey analysis activities include laboratory analysis, soil classification, and statistical data analysis to test the correlation between land characteristics with garlic production. Results of the research showed that land of garlic in Pujon District has Inceptisols and Alfisols. The land characteristics in Pujon district has difference, among others, land elevation are 861â€“1.213 mdpl, slope of land are 3â€“36%, soil texture are â€œloamâ€ to â€œclay â€œ, soil aggregate are â€œvery-stableâ€, soil pH ranging from very acid to semi acid, soil CEC are â€œmoderateâ€ to â€œvery-highâ€, and the base saturation are â€œlowâ€ to â€œvery-highâ€. The relationship between land characteristics to crop production, proved by correlation between variable such as elevation (r =-0.559), CEC (r =-0.515), base saturation (r = 0.561), % sand fraction (r = 0.541), and % clay fraction (r = -0.675). Other factors affecting garlic production are varieties of garlics and soil tillage, these correlation are not significant.